2020
DOI: 10.1108/jea-02-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Undoing systems of exclusion: exploring inclusive leadership and systems thinking in two inclusive elementary schools

Abstract: PurposeMost education systems were not initially designed to include students with disabilities. However, over the past 25 years, great strives have been taken to ensure students with disabilities have access to the general education classroom and to important social, emotional and academic opportunities. Within the USA, researchers have begun to focus on the principal's role in creating and sustaining effective inclusive schools. The purpose of this article is to examine the leadership practices and perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…They need to make the incluscive education planing, develop and revising the plan according to the condition (DeMatthews, 2021) and redesign the organization for inclusive education (Waldron et al, 2011). For instance, the objective and impartial school selfevaluation is a kind of effective system in inclusive education (Fitzgerald & Radford, 2022;DeMatthews, 2021;Yazicioglu, 2021). And using data as the basis for all decision making (Waldron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They need to make the incluscive education planing, develop and revising the plan according to the condition (DeMatthews, 2021) and redesign the organization for inclusive education (Waldron et al, 2011). For instance, the objective and impartial school selfevaluation is a kind of effective system in inclusive education (Fitzgerald & Radford, 2022;DeMatthews, 2021;Yazicioglu, 2021). And using data as the basis for all decision making (Waldron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance professional abilities, principals need professional training to develop their understanding of inclusive education development (Mohanty & Nanda, 2017;Fitzgerald & Radford, 2022). DeMatthews found that learning leadership knowledge is effective for principals to enhance inclusive education leadership skills (DeMatthews, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Implementing this practical work is a form of collaboration between IESs and universities. One of the collaborative relationship goals of IESs is to ensure that STs have quality competencies (i.e., pedagogic, personal, professional, and social competencies) to teach at IESs (DeMatthews, 2020;Nishina et al, 2019;Santos et al, 2016). For this reason, this collaborative relationship between IESs and universities needs to be maintained, continuously and sustainably, so that IESs experience long-term impact and benefits (Ferguson-Patrick, 2020;Buchs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%